2007
DOI: 10.1172/jci31494
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of prostate cancer genetic risk by omega-3 and omega-6 fatty acids

Abstract: Although a causal role of genetic alterations in human cancer is well established, it is still unclear whether dietary fat can modulate cancer risk in a predisposed population. Epidemiological studies suggest that diets rich in omega-3 polyunsaturated fatty acids reduce cancer incidence. To determine the influence of fatty acids on prostate cancer risk in animals with a defined genetic lesion, we used prostate-specific Pten-knockout mice, an immune-competent, orthotopic prostate cancer model, and diets with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
206
1
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(222 citation statements)
references
References 47 publications
10
206
1
5
Order By: Relevance
“…For example, based on an extensive body of literature indicating that dietary restriction is anti-tumorigenic, analyses of dietary restriction or low-fat diets on cancer progression in genetically engineered mice has revealed the PI3K-Akt signaling pathway as a molecular target for these dietary interventions (Berquin et al 2007;Kobayashi et al 2008;Kalaany and Sabatini 2009). Another promising agent is vitamin D, which has been suggested by ample epidemiological evidence to protect against tumorigenesis, but has displayed variable efficacy in clinical trials (Deeb et al 2007).…”
Section: Dietary and Lifestyle Factors In Cancer Preventionmentioning
confidence: 99%
“…For example, based on an extensive body of literature indicating that dietary restriction is anti-tumorigenic, analyses of dietary restriction or low-fat diets on cancer progression in genetically engineered mice has revealed the PI3K-Akt signaling pathway as a molecular target for these dietary interventions (Berquin et al 2007;Kobayashi et al 2008;Kalaany and Sabatini 2009). Another promising agent is vitamin D, which has been suggested by ample epidemiological evidence to protect against tumorigenesis, but has displayed variable efficacy in clinical trials (Deeb et al 2007).…”
Section: Dietary and Lifestyle Factors In Cancer Preventionmentioning
confidence: 99%
“…BAD is dephosphorylated in response to ZD1839, and primary mammary epithelial cultures derived from BAD-deficient mice proved resistant to the toxic effect of this drug. Likewise, loss-of-function studies in a mouse model of prostate cancer underscored a physiologically relevant role for BAD in tumor regression induced by omega-3 and omega-6 polyunsaturated fatty acids (Berquin et al, 2007). While BAD phosphorylation is a component of the survival program driven by the oncogenic activation of select kinases, BAD dephosphorylation may contribute to the pro-apoptotic effects of certain tumor suppressors.…”
Section: Bad and Tumor Cell Apoptosismentioning
confidence: 99%
“…Furthermore, to determine the influence of n-6 and n-3 fatty acids on prostate cancer risk in animals with a defined genetic lesion (Pten-deletion), Chen and his colleagues crossed the fat-1 mice with prostate-specific Pten-knockout mice (a prostate cancer model) to generate compound mice (Pten-knockout plus fat-1) (10). They found that the hybrid mice (Pten-knockout plus fat-1, which have higher levels of n-3 fatty acids) had a significantly lower rate of tumor growth and survived longer compared to Pten-knockout mice (without fat-1) (10). Tumors from mice with high n-3 had lower proportions of phosphorylated Bad, resulting in increased cell apoptosis (10).…”
Section: Recent Studies Utilizing the Fat-1 Micementioning
confidence: 99%